Incidence of neurosensory deficits following surgical removal of mandibular third molars: a prospective clinical study - M. I., Thaufiq Ahamed; Jayakumar, Naveen; R. S., Neelakandan (International Journal of Research in Medical Sciences, 2019)
Background: The aim of this prospective study was to determine the incidences of inferior alveolar nerve and lingual nerve deficit following surgical removal of impacted mandibular third molars and to evaluate the risk factors responsible for these postoperative neurosensory deficits. Methods: A total of 80 patients who reported to department of oral and maxillofacial surgery, Meenakshi Ammal Dental College, Chennai, Tamil Nadu, India requiring surgical removal of impacted mandibular third molar were included in this cross-sectional study. Standard surgical procedure was performed. All patients were reassessed one week post-surgery. Subjectively reported altered sensations were recorded and objective assessments were performed with light touch test, two-point discrimination threshold and pin-pick pain threshold. The collected data was analyzed using the chi square test to find out any clinical relevance. Results: There was no inferior alveolar nerve related neurosensory deficits and 6 (7.5%) resulted in lingual nerve related neurosensory deficits. The incidence of LN deficit for mesioangular, horizontal, distoangular was 1.3%, 3.8% and 2.5% respectively. Type of impaction assumed a mild statistical significance (p = 0.050). Conclusions: This study highlights the importance of careful preoperative clinical and radiographic assessment of patients where third molar surgery is planned. The surgical technique of third molar removal is also likely to have great impact on the outcome.